Le vocabulaire militaire dans le corpus français-slovene FraSloK - Mezeg, Adriana (Linguistica (Ljubljana), 2018)
This article studies the use of military vocabulary in the French-Slovene parallel corpus FraSloK, which contains texts published between 1995 and 2009. Taking into account the frequency of occurrences of the word guerre(s) (war(s)) in the French source texts, the journalistic subcorpus composed of 300 articles from Le Monde diplo-matique and three novels from the literary subcorpus turned out to be interesting for our research. On the basis of the lists of all words used, we manually extracted all the nouns belonging to the military field (3,735 occurrences for 289 different words). Using French and Slovene monolingual dictionaries, the classification per register of language shows a predominance of the standard variety in French, even though certain words are highly specialised. Interestingly, in the main Slovene dictionary several cor-responding items are lablled as non-standard (military, jargon, military jargon, etc.). Moreover, the corpus contains many foreign words or borrowings, whereas elements of other language registers (obsolete, informal, colloquial, modern, politics, old-fash-ioned, etc.) are only used sporadically. There are almost no words labelled as militaryor slang/jargon. The article identifies the wars about which the French FraSloK texts speak, classifies the French lexis used into five categories and, finally, specifies the strategies employed in the translation of military vocabulary into Slovene
Keywords: francoščina; jezikovne zvrsti; prevajanje; slovenščina; vojaško besedišče; vojni besednjak; vzporedni korpus